A Non-Coercive Leasing Debt Enforcement Model: Reconceptualizing Compliance through Blockchain-Based Systems - Nanin Koeswidi Astuti (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2026)
Debt collection in motor vehicle financing in Indonesia continues to rely heavily on coercive practices carried out by third-party actors commonly known as mata elang (matel). These methods do more than raise questions of civil liability; they frequently spill over into social conflict and serious criminal law risks, as illustrated by recurring incidents of violence resulting in loss of life and broader public harm. Such conditions point to a deeper, systemic failure in the enforcement of credit agreements—one that has evolved through informal mechanisms and operates with fragile legal legitimacy. This study undertakes a normative examination of the structural weaknesses inherent in coercive debt collection practices and advances a non-coercive enforcement model grounded in blockchain technology. Using a normative legal methodology supported by conceptual and analytical approaches, the research explores issues of legitimacy, criminal liability risk, legal certainty, and the role of the state in enforcing credit obligations. The findings suggest that blockchain-based enforcement offers a transparent, automated, and institutionalized contractual framework that replaces physical force and social intimidation with systemic compliance. Rather than sidelining the state, this model strengthens state involvement through regulatory oversight and institutional validation, fostering a more legitimate, proportionate, and rule-of-law-oriented approach to obligation enforcement.